Effects of psychedelics on brain plasticity – a review of current research and the possibility of therapeutic use in psychiatry (Engrami, 2025)
Psychedelics are psychoactive substances that cause changes in perception, state of consciousness, mood and numerous cognitive processes. The best known are lysergic acid diethylamide (LSD), N,N-dimethyltryptamine (DMT), psilocybin and mescaline. The main mechanism of action of psychedelics is agonism towards serotonin 5-HT2A receptors. In the middle of the 20th century, interest in the use of psychedelics in psychiatry arose, but due to political pressure and the potential danger of uncontrolled use, they were banned in the 1970s. In the absence of innovations in treatment and new psychopharmacological agents, the potential of psychedelics in the treatment of mental illnesses has again been the focus of research in recent decades. In this paper, the neurobiology of psychedelics will be presented in the light of current research on their effects on neural networks and neuroplasticity, and therefore the possibilities of therapeutic application in psychiatry. Also, recent research will be presented with an emphasis on randomized double-blind placebo-controlled studies in which the effectiveness of the use of psychedelics in the treatment of depression and disorders caused by the use of alcohol and other psychoactive substances was examined. Findings so far indicate that psychedelics may be a promising new approach for the treatment of mental illness, but the use of psychedelics for these purposes raises not only bioethical, but also new legal issues.
Keywords: psychodelics; neruoplasticity; depression; addiction; LSD; psylocibin